Trend Analysis of Rainfall in Ziz Basin in Southeastern of Morocco, for Period (1960-2019) (Libya Journal of Geographical Studies, 2023)
This research aims to Identify the trends of fluctuation in the annual precipitation rates, whether upwards or downwards, and to know the values of their deviations from the general trend line for a period of 60 years (1960 – 2019), using a set of indicators; Including moving averages (10 years linear regression equation (the least squares), then Mann and Kendall test.The results showed that all stations plotted two directions after using all indicators; The first towards a slight increase, and it is linked to the stations located in the upper basin of the Ziz ; Including the stations (Fom Teleshet with +0.03, Mzizel with +0.16, then Errachidia station with +0.017), while the rest of the stations in the basin recorded a trend towards decreasing .It turned out that rainfall trends cannot be relied upon to establish irrigated agricultural projects in the basin, except after finding alternative water sources, such as building large dams to store water in rainy years.
Keywords: Ziz Basin; Oasis; Rainfall; Trend Analysis; Mann-Kendall test; Moving Averages